2020
DOI: 10.1101/2020.01.18.911362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AAV Ablates Neurogenesis in the Adult Murine Hippocampus

Abstract: Recombinant adeno-associated virus (rAAV) has been widely used as a viral vector across mammalian biology and has been shown to be safe and effective in human gene therapy. We demonstrate that neural progenitor cells (NPCs) and immature dentate granule cells (DGCs) within the adult murine hippocampus are particularly sensitive to rAAV-induced cell death. Cell loss is dose dependent and nearly complete at experimentally relevant viral titers. rAAV-induced cell death is rapid and persistent, with loss of BrdU-la… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 115 publications
0
11
0
Order By: Relevance
“… 36 We found no cells in the GC layer three weeks after infection ( Figure 1 C), consistent with a recent report showing a high sensitivity to AAV-induced cell death specific for immature dentate GCs. 37 Only a small number of pyramidal cells in the CA3 area (7% of all labeled cells) expressed mCherry ( Figures S1 A and S1B). These results indicate that the vast majority of targeted cells in our approach are ventral MCs.…”
Section: Resultsmentioning
confidence: 99%
“… 36 We found no cells in the GC layer three weeks after infection ( Figure 1 C), consistent with a recent report showing a high sensitivity to AAV-induced cell death specific for immature dentate GCs. 37 Only a small number of pyramidal cells in the CA3 area (7% of all labeled cells) expressed mCherry ( Figures S1 A and S1B). These results indicate that the vast majority of targeted cells in our approach are ventral MCs.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work 73 has reported that rAAVs impair neurogenesis in the adult mouse DG, with significant implications for functional recordings of GCs relying on rAAV for delivery of a genetically encode actuators or sensors. Given the design of our study, we believe these findings have limited relevance to the work presented here: principally, Johnston and colleagues 73 found that cells born two weeks or more prior to viral injection demonstrate no reduction, and in our study induction of Nestin expression by TMX occurred 2-3 weeks prior to injection with AAV1.Syn. GCaMP6f.…”
Section: Discussionmentioning
confidence: 99%
“…Among the qualities that make them good vectors, it is important to highlight that they are nonintegrative, nonpathogenic, and nonimmunogenic in humans, and have the capacity to infect nondividing cells providing long-term expression. However, a recent study shows that AAV can induce cell death in some neural cell types in the murine hippocampus, suggesting that these approaches should be carefully evaluated [ 110 ]. Nevertheless, in the last few years, several reports have been published concerning AAV-mediated therapy using different virus serotypes and delivery strategies.…”
Section: Therapeutic Approachesmentioning
confidence: 99%